URGENSI PENERAPAN ISLAMIC CORPORATE GOVERNANCE DI BAITUL MAAL WAT TAMWIL (BMT) - Muh Awal Satrio Nugroho (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
Islamic corporate governance model in Islam has its own unique features and presents distinctive characteristics in comparison with the western concept .Unlike the western concept of corporate governance which is based on the western business morality that derived from secular humanist, the corporate governance in Islamic Financial Institutions is founded on the epistemological aspect of Tawhid,sharia, and ethics.Baitul Maal Wat Tamwil (Islamic micro finance) have to apply Islamic Corporate Governance in order to become the strong and succesfull institution